Soft landing control of unmanned powered parafoils in unknown wind environments. (March 2019) - Luo, Shuzhen; Sun, Qinglin; Tan, Panlong; Sun, Mingwei; Chen, Zengqiang; He, Yingping
For autonomous landing powered parafoils, the ability to perform a final flare maneuver against the wind direction can generate a considerable reduction of lateral and longitudinal velocities at impact, enabling a soft landing for a safe delivery of sensible loads. To realize accurate, soft landing in the unknown wind environment, an in-flight wind identification algorithm is first proposed. The wind direction and speed can be obtained online by only using the GPS sampling data based on the recursive least square method. Moreover, the 3D trajectory tracking strategy for the powered parafoil is also established, which is globally asymptotically stable. Furthermore, the lateral trajectory tracking controller and longitudinal altitude controller based on active disturbance rejection control are presented, respectively. Eventually, results from simulations demonstrate that the proposed landing control method can effectively realize accurate soft landing in unknown wind environments with the in-flight wind identification algorithm applied in the trajectory tracking process.